Financial Inclusion and Bank Profitability: Evidence from Indonesia - Rakotoarisoa Maminaina Heritiana Sedera; Tastaftiyan Risfandy; Inas Nurfadia Futri (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study attempts to investigate the effect of financial inclusion on bank profitability in the Indonesian context.Design/Methodology/Approach: The sample of this study consisted of 93 commercial banks in Indonesia between 2015 and 2020. The researchers used panel data regression with a fixed effects approach to investigate the nexus between financial inclusion and bank profitability.Research findings: It was found that financial inclusion positively affected bank profitability in three different dimensions of financial inclusion: access, availability, and usage.Theoretical contribution/Originality: Most of the previous papers have investigated the impact of financial inclusion on the national levels, such as how financial inclusion affects economic growth. Meanwhile, this paper examines the impact of financial inclusion on bank-level profitability, an issue relatively unexplored in the literature, particularly in Indonesia. The use of three dimensions of financial inclusion in the context of a developing economy is also the novelty of this article.Practitioner/Policy implication: The result of this study can also assist policymakers, such as the central bank of Indonesia, in designing better strategies and regulations to achieve higher financial inclusion and boost the economy's development.Research limitation/Implication: The result of this paper might only be applied to Indonesia’s specific setting or developing countries.